iACT4IBD: a randomised controlled trial of a brief online intervention based on acceptance and commitment therapy to improve wellbeing for adults with inflammatory bowel disease - Lin, Karen; Cavadino, Alana; Ow, Maggie; Douglas, Meihana; Serlachius, Anna (Frontiers in Digital Health, 2025)
IntroductionInflammatory bowel disease (IBD) is associated with high rates of depression and anxiety. Acceptance and Commitment Therapy (ACT) has demonstrated utility across different chronic health conditions, and online ACT interventions may potentially improve access to mental health support.MethodsThis study was a parallel two-arm randomised controlled trial that investigated the effects a brief seven-day online ACT intervention (iACT4IBD) on psychological and physical health outcomes. We examined whether iACT4IBD could reduce depressive symptoms in adults with IBD compared to a waitlist control group at 4-weeks follow-up. Effects of iACT4IBD on levels of anxiety, stress, wellbeing, quality of life, and IBD activity were also explored. Seventy adults with IBD (Crohn's disease and ulcerative colitis) were randomly allocated to either the iACT4IBD intervention or a waitlist control group. Psychological and physical health outcomes were collected at baseline, 4-weeks and 8-weeks after baseline. Outcome measures were assessed at baseline and 4-weeks follow-up using mixed ANOVAs.ResultsNo between-group differences in psychological outcomes were found from baseline to 4-weeks follow-up. Crohn's disease activity scores in the intervention group were significantly lower after 4-weeks compared to the waitlist control group. Qualitative feedback suggested that the intervention was acceptable and beneficial.DiscussionThere were no improvements to mental wellbeing; however, findings provided some support for the intervention improving physical health in people with Crohn's disease. Further research is needed.Clinical Trial RegistrationAustralian New Zealand Clinical Trials Registry (U1111-1282-2334).